Developing and Validating Pre-Service EFL Teachers’ Grit Scale: Evidence from Indonesia - Arfiandhani, Puput; Takeuchi, Osamu (Journal of Foreign Language Teaching and Learning, 2000)
Background: Training to become an English teacher can be challenging for pre-service non-native English language teachers. In L2 English settings, they need to play a unique dual role as L2 teachers-in-training and L2 learners. Unlike trainees in other subjects, EFL teacher trainees use the target language they are still learning as the medium of instruction. Grit, a positive psychology concept referring to passion and perseverance, may help explain their perseverance and passion to become future EFL teachers. However, a specific grit scale to measure pre-service EFL teachers’ grit is still unavailable. Objective: The purpose of the present study is to develop and validate a pre-service EFL teachers’ (PET) grit scale. The scale was designed to measure pre-service EFL teachers’ grit to become English language teachers. Methods: To develop and validate the scale, an Exploratory Factor Analysis (EFA) (n = 117) and a Confirmatory Factor Analysis (CFA) (n = 149) were conducted. Participants were final year pre-service EFL teachers in a private teacher training institution in Indonesia. Findings: The self-report questionnaire comprised 11 items which were categorized into three subscales: passion for professional development, perseverance for professional development, and determination to become English teachers. The results indicated that the scale demonstrated moderate fit indices (RMSEA = .081; CFI = .92; TLI = .89; SRMR = .079, RNI = .92) with a chi-square value of χ² = 81.077 (df = 41). Furthermore, the empirical findings suggested that the newly designed instrument was valid and reliable (ω = 0.81; α = 0.80) for measuring pre-service EFL teachers’ grit. Conclusion: The present study provides a valid and reliable measurement tool to evaluate the success of pedagogical interventions targeting grit among pre-service EFL teachers. For example, the scale can be utilized to identify pre-service EFL teachers who may need additional support to sustain their grit during challenging phases (e.g., teaching practicum, early stages of teacher training), thus enabling targeted interventions aimed at improving their grit levels. PET-Grit which can help improve teacher training programs and contribute to the growing body of research in this area. Theoretically, the present study highlights the complexity of pre-service EFL teachers' dual roles as both L2 learners and future L2 teachers, demonstrating that grit manifestation is culturally and contextually sensitive, thereby supporting the need for context-sensitive psychological constructs in applied linguistics.